Política del reconocimiento y tipos de ciudadanía - Esteban Enguita, José Emilio (Logos. Anales del Seminario de Metafísica, 2007)
The concern of this article is with the crisis of the concept of citizenship due to the social and political changes taking place in our societies. I shall focus on those problems caused by multiethnic, multicultural and multinational nature of present societies and by demands of nationalism and what has come to be know as the politics of “multiculturalism”. These pages attempt to offer a taxonomy of citizenship types as well as a criterion by which to distinguish between acceptable and unacceptable varieties of citizenship.